WOMEN EMPOWERMENT, MICROFINANCE AND POVERTY NEXUS: AN EMPIRICAL ESTIMATION PERSPECTIVE - Ali, Ghaffar; Yaseen, Asma; Bashir, Muhammad Khalid; Adil, Sultan Ali; Hassan, Sarfraz (PEOPLE: International Journal of Social Sciences, 2015)
Deprivation and poverty are worldwide challenges for poorer countries. Poor people especially women were excluded from financial services until microfinance institutions (MFIs) emerged. During the past few decades microcredit has enjoyed tremendous growth and women continue to be the major beneficiaries. The main objective of this study is to check weather microfinance helped women to attain decent work and strengthen their empowerment or not. This study is based on primary data and respondents were taken from First Microfinance Bank. A sample of 125 respondents was taken through simple random sampling. The study area was Faisalabad.SPSS 22 software was used for analysis. Logit model was applied to get and analyze results. Results showed significant positive relationship between women empowerment and different socio-economic independent variables i.e. income, investment, self-confidence, free movement. All the variables are statistically significant other than education. It is cleared that women enjoy more freedom, self-confidence and learn more skills to enhance their income. By investing in people and empowering individual women and men with education and generation of equal opportunities can create the conditions to allow the poor to break out of the poverty.